2018
DOI: 10.1021/acsami.8b08450
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental Stiffness Regulates Dental Papilla Cell Differentiation: Implications for the Importance of Fibronectin–Paxillin−β-Catenin Axis

Abstract: The mechanical stiffness of substrates is recognized to be an important physical cue in the microenvironment of local cellular residents in mammalian species due to their great capacity in regulating cell behavior. Dental papilla cells (DPCs) play an important role in the field of dental tissue engineering for their stem cell-like properties. Therefore, it is essential to provide the suitable microenvironment by combining with the physical cues of biomaterials for DPCs to carry out the function of effective ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 44 publications
(79 reference statements)
3
19
1
Order By: Relevance
“…The role of FAK and paxillin in green has been elucidated in our previous data. 19,34 The grey parts are involved in the vinculin-cytoskeleton rearrangements but not in our study…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…The role of FAK and paxillin in green has been elucidated in our previous data. 19,34 The grey parts are involved in the vinculin-cytoskeleton rearrangements but not in our study…”
Section: Discussioncontrasting
confidence: 63%
“…33 Surface roughness could also influence cell functions, such as cell migration, cell proliferation and differentiation. 34 For hydrophilicity, Sun et al 35 systematically summarized and illustrated the biological processes influenced by the hydrophilicity from structural biointerface materials and smart biointerface materials. Menon et al 36 found that the migration of human bone marrow-derived mesenchymal stem cells (hBMSCs) was greatly enhanced when cells were seeded on the PDMS substrate with intermediate levels (1:20) and that the proliferation was increased when the cells were seeded on the PDMS substrate with a higher stiffness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibronectin, as the ligand for a dozen members of the integrin receptor family, could bind paxillin to achieve the transduction of environmental signals to the cell interior. [31] After plated on fibronectin, U2OS cells-localized focal adhesion sites displayed a punctate distribution with bright green fluorescence (Figure 7c). When staining the edited cells with monoclonal paxillin antibody and Alexa Fluor@647-conjugated goat anti-rabbit lgG (which was predicted to label both the GFP-tagged and untagged paxillin protein factions within the same cells), obvious colocalization of different fluorescence channels (paxillin, red and GFP, green) was observed in Figure 7c.…”
Section: In Vitro Gene Knock-inmentioning
confidence: 97%
“…[29] Therefore, mutation in the PXN gene, as well as abnormal expression of paxillin protein, has been implicated in the progression of various cancers. [30,31] For this purpose, nuclear localization sequence (NLS)-conjugated MSNs were prepared, which could further immobilize the plasmids with high loading efficiency (50%). After pH-responsive polymer (poly(dimethyldiallylammonium chloride), PDDA) coating in water assisted by microfluidic technology, the positively charged nanocarrier can efficiently protect loaded plasmids, and subsequently it can enhance the cellular internalization and endosomal escape.…”
Section: Introductionmentioning
confidence: 99%